Optimization and Experimental Validation of Amorphous Alloy High-Speed Asynchronous Motor for Simultaneous Reduction on Core and Copper Losses - Jiahao Zhang; Ronggao Cui; Yu Wei; Degui Yu; Shunde Xie; Shitong Fang; Jun Shen (IEEE Access, 2023)
Amorphous alloy has been proposed to replace silicon steel as the stator core material of high-speed asynchronous motors so as to reduce their core losses. However, it is found that this is at the expense of increasing the copper loss. Therefore, the optimization of amorphous alloy high-speed asynchronous motors is needed to simultaneously reduce their core and copper losses, which is still an open issue. This paper uses an evolutionary algorithm to achieve this and provides the experimental validation. Firstly, the modeling and finite element simulation of the asynchronous motors with the stator core materials as the amorphous alloy and silicon steel are presented and compared. Secondly, with the knowledge of the optimization objectives of the amorphous alloy asynchronous motor, the evolutionary algorithm is proposed to optimize the shapes of its stator and rotor slots. The related mechanisms are discussed based on the electromagnetism. Thirdly, the experimental validation is conducted. Results show that compared with the silicon steel asynchronous motor (Motor-S) and the amorphous alloy asynchronous motor before optimization (Motor-A), the optimized Motor-A (Motor-AO) has the largest high-efficiency range of output torque and operational speed. Specifically, its efficiency at the output torque of 1.5 $\text{N}· \text{m}$ and the operational speed of 7000 rpm is increased by 4.29% and 7.12% compared with those of Motor-A and Motor-S, respectively. In addition, the temperature distribution shows that the case and rotor temperatures of Motor-AO is the lowest, indicating its superior comprehensive performance.